2019
DOI: 10.21608/ejabf.2019.24189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methyl Farnesoate Administration on Ovarian Growth and Maturation in the Freshwater Crab Travancoriana schirnerae

Abstract: This study assessed the effect of exogenous administration of methyl farnesoate on growth and maturation of ovary in the freshwater crab Travancoriana schirnerae. Results provide strong evidence that methyl farnesoate administration induced ovarian growth in all phases of oogenesis as judged by the increased ovarian indices, oocyte diameter and oocyte proportion values of experimentals over controls. Our observations also revealed that methyl farnesoate treatment induced avitellogenic and previtellogenic ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Nauplius, 30: e2022006 reproductive system. The results of this study are consistent with the results of other studies on other decapod species (Nagaraju et al, 2004;Alfaro et al, 2008;Raghavan and Ayanath, 2018). Further research should be carried out to determine the effect of MF injection on reproductive endocrine metabolism, gamete composition (e.g., protein and lipid profiles) and histology of different regions of the vas deference to assess changes in quantities and ratios of cell types in male reproductive tracts in crayfish.…”
Section: Methyl Farnesoate Injection In Crayfishsupporting
confidence: 90%
See 1 more Smart Citation
“…Nauplius, 30: e2022006 reproductive system. The results of this study are consistent with the results of other studies on other decapod species (Nagaraju et al, 2004;Alfaro et al, 2008;Raghavan and Ayanath, 2018). Further research should be carried out to determine the effect of MF injection on reproductive endocrine metabolism, gamete composition (e.g., protein and lipid profiles) and histology of different regions of the vas deference to assess changes in quantities and ratios of cell types in male reproductive tracts in crayfish.…”
Section: Methyl Farnesoate Injection In Crayfishsupporting
confidence: 90%
“…MF is included in several hormonal processes in crustaceans. There are studies showing that MF induces gonadal development in some decapods (Alfaro et al, 2008;Marsden et al, 2008;Nagaraju and Borst, 2008;Zaleski and Tamone, 2014;Hemalatha et al, 2016;Raghavan and Ayanath, 2018). For example, gonadal development of decapods induced by MF has been reported in the estuarine female crab Neohelice granulata (Dana, 1851) (see Medesani et al, 2015) and freshwater crab Oziothelphusa senex senex (Fabricus, 1798) (see Reddy and Reddy, 2015) and Alfaro et al (2008) found that MF has an effect on spermatophore quality in the white shrimp, Litopenaeus vannamei (Boone, 1931).…”
Section: Methyl Farnesoate Injection In Crayfishmentioning
confidence: 99%
“…In contrast, MF levels did not change with maturation in M. rosenbergii , but were correlated with molting ( 129 ) and MF was also demonstrated to inhibit late ovarian stage development with reduced fecundity levels in P. monodon ( 130 ). MF injection during the late vitellogenic phase had no significant effect on post-vitellogenesis or spawning in the freshwater crab Travancoriana schirnerae ( 131 ). Nevertheless, dietary inclusion of MF stimulated vitellogenesis in the crayfish P. clarkii and P. monodon , bringing about increased oocyte diameter, higher fecundity and egg fertility, and increased hatching rates ( 123 , 132 ).…”
Section: Methyl Farnesoate (Mf)mentioning
confidence: 94%
“…In addition to the important roles played in the regulation of moulting, larval development and morphogenesis (Abdu et al, 1998;Reddy et al, 2004), MF, the crustacean equivalent of the juvenile hormone III of insects, functioned as a gonadotropin. The gonadotropic effect of MF and farnesoic acid (precursor to MF) has been reported in a number of crustaceans (Rodriguez et al, 2002;Mak et al, 2005;Tiu et al, 2006;Balasubramanian et al, 2010;Reddy and Reddy, 2015;Hemalatha et al, 2016;Sudha Devi and Aswani, 2018;Muhd-Farouk et al, 2019). In vitro studies by Otsu (1963) reported that MF promoted the development of oocyte and Vg messenger in the hepatopancreas and ovary.…”
Section: Introductionmentioning
confidence: 97%